2013
DOI: 10.1016/j.devcel.2013.02.013
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Genetic Pathway Determines Inflorescence Architecture in Arabidopsis and Rice

Abstract: The spatiotemporal architecture of inflorescences that bear flowers determines plant reproductive success by affecting fruit set and plant interaction with pollinators. The inflorescence architecture that displays great diversity across flowering plants depends on developmental decisions at inflorescence meristems. Here we report a key conserved genetic pathway determining inflorescence architecture in Arabidopsis thaliana and Oryza sativa (rice). In Arabidopsis, four MADS-box genes, SUPPRESSOR OF OVEREXPRESSI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
165
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(167 citation statements)
references
References 61 publications
2
165
0
Order By: Relevance
“…The best matches of Glyma18g50910 in Arabidopsis were the three floral homeotic MADS domain factor genes, which were the fruit tissue identity gene FRUITFUL (FUL) (Gu et al, 1998), the floral meristem identity gene APETALA1 (AP1) (Gustafson-Brown et al, 1994;Liljegren et al, 1999), and the floral regulatory gene CAULIFLOWER (CAL) (Kempin et al, 1995) (Figure 2; Supplemental Figure 1). It has been demonstrated that AP1 and another floral identity gene, LEAFY (LFY; Weigel et al, 1992), antagonize TFL1, the functional ortholog of the soybean Dt1, to regulate the fate of lateral meristems at the inflorescence apex in Arabidopsis (Bradley et al, 1997;Liljegren et al, 1999;Ratcliffe et al, 1999;Liu et al, 2009Liu et al, , 2013. These findings, along with all of our foregoing observations, including the deduced interaction between Dt2 and Dt1 and the mapping of Dt2, suggest that Glyma18g50910 was most likely to be the candidate for the Dt2 locus.…”
Section: Prediction Of the Dt2 Candidate By Interspecific Comparisonmentioning
confidence: 99%
“…The best matches of Glyma18g50910 in Arabidopsis were the three floral homeotic MADS domain factor genes, which were the fruit tissue identity gene FRUITFUL (FUL) (Gu et al, 1998), the floral meristem identity gene APETALA1 (AP1) (Gustafson-Brown et al, 1994;Liljegren et al, 1999), and the floral regulatory gene CAULIFLOWER (CAL) (Kempin et al, 1995) (Figure 2; Supplemental Figure 1). It has been demonstrated that AP1 and another floral identity gene, LEAFY (LFY; Weigel et al, 1992), antagonize TFL1, the functional ortholog of the soybean Dt1, to regulate the fate of lateral meristems at the inflorescence apex in Arabidopsis (Bradley et al, 1997;Liljegren et al, 1999;Ratcliffe et al, 1999;Liu et al, 2009Liu et al, , 2013. These findings, along with all of our foregoing observations, including the deduced interaction between Dt2 and Dt1 and the mapping of Dt2, suggest that Glyma18g50910 was most likely to be the candidate for the Dt2 locus.…”
Section: Prediction Of the Dt2 Candidate By Interspecific Comparisonmentioning
confidence: 99%
“…This allows us to speculate as to how the different TFL1 expression phases could be established. MADS-box factors SOC1, AGL24, SVP and SEP4, which bind through interaction with AP1 to sequences that are present in cisregulatory regions II and III, have been shown to contribute to TFL1 repression in flowers (Kaufmann et al, 2010;Liu et al, 2013). This would explain why ectopic TFL1 expression in flowers is observed when these regions are deleted.…”
Section: Regulatory Regions Sufficient For Tfl1 Expressionmentioning
confidence: 99%
“…poorly understood. Several regulators of its expression have been identified, most of them involved in the repression of TFL1 expression in flowers (Kaufmann et al, 2010;Moyroud et al, 2012;Winter et al, 2011;Liu et al, 2013;Pérez-Ruiz et al, 2015); nevertheless, little is known about the structure of the cis-regulatory regions that are targeted, apart from the observation that sequences in the 3′ intergenic region are important for TFL1 function (Ohshima et al, 1997;Kaufmann et al, 2010). Flowering time pathways are responsive to the environment and affect TFL1 expression, but again no model describes how they integrate TFL1 expression at the genomic level.…”
Section: Introductionmentioning
confidence: 99%
“…A further rice antiflorigen RICE CENTRORADIALIS4 (RCN4) enhances panicle branches when it is ectopically expressed but RCN knock down lines produced considerably smaller panicles in rice because of the reduced number of branches. Rice orthologs of SEP4, AGL24, SOC1, and SVP regulate panicle structure because knock down lines of these genes increase the number of panicle branches and also show ectopic expression of RCN4 (Liu et al 2013). These results indicate that panicle branching is determined by rice orthologs of SEP4, AGL24, SOC1, and SVP through suppressing antiflorigen RCNs in the lateral meristems of rice.…”
Section: Rice Shoot Structure Controlled By Florigen Pathwaysmentioning
confidence: 84%
“…It is suggested that FD plays pivotal roles in the control of floral transition by interacting with FT or TFL1 (Hanano and Goto 2011). Interestingly, AP1 and LFY directly repress TFL1 transcription in lateral floral meristems and TFL1 suppresses MADS-box genes, including AP1, SOC1, AGL24, SVP, and SEP4 (Liu et al 2013). Therefore, the main axes continuously produce lateral flowers and lateral branches that reiterate the inflorescence habit ( Fig.…”
Section: Arabidopsis Shoot Structure Controlled By Florigen and Antifmentioning
confidence: 96%